Peningkatan Keaktifan Dan Hasil Belajar IPS Siswa Melalui Model Pembelajaran Kooperatif Tipe Group Investigation Pada Siswa Kelas V SD - Amirullah Amirullah (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
The purpose of this study was to determine the increase in social studies theme learning outcomes through the cooperative learning model of the group investigation type in Class V students of SD Inpres Pacekke, Soppeng Riaja District, Barru Regency. The research method used is classroom action research, this research is an activity cycle consisting of two cycles. Each cycle includes planning, action, observation and reflection. The conclusion in this research is that the application of cooperative learning through group investigation can improve student social studies learning outcomes. Where the average value of students each cycle has increased. In cycle I, the average student score was 79.30. In cycle II the average student score was 93.30, this showed a significant increase.